Toward a Neurophysiological Theory of Auditory Stream Segregation. - Snyder, Joel S.; Alain, Claude (Psychological Bulletin, 2007)
Auditory stream segregation (or streaming) is a phenomenon in which 2 or more repeating sounds differing in at least 1 acoustic attribute are perceived as 2 or more separate sound sources (i.e., streams). This article selectively reviews psychophysical and computational studies of streaming and comprehensively reviews more recent neurophysiological studies that have provided important insights into the mechanisms of streaming. On the basis of these studies, segregation of sounds is likely to occur beginning in the auditory periphery and continuing at least to primary auditory cortex for simple cues such as pure-tone frequency but at stages as high as secondary auditory cortex for more complex cues such as periodicity pitch. Attention-dependent and perception-dependent processes are likely to take place in primary or secondary auditory cortex and may also involve higher level areas outside of auditory cortex. Topographic maps of acoustic attributes, stimulus-specific suppression, and competition between representations are among the neurophysiological mechanisms that likely contribute to streaming. A framework for future research is proposed. Reprinted by permission of the publisher.